2008
DOI: 10.1007/s12012-008-9020-4
|View full text |Cite
|
Sign up to set email alerts
|

Potent Induction of Total Cellular and Mitochondrial Antioxidants and Phase 2 Enzymes by Cruciferous Sulforaphane in Rat Aortic Smooth Muscle Cells: Cytoprotection Against Oxidative and Electrophilic Stress

Abstract: Sulforaphane, a cruciferous isothiocyanate compound, upregulates cytoprotective genes in liver, but its effects on antioxidants and phase 2 defenses in vascular cells are unknown. Here we report that incubation of rat aortic smooth muscle A10 cells with sulforaphane (0.25-5 microM) resulted in concentration-dependent induction of a spectrum of important cellular antioxidants and phase 2 enzymes, including superoxide dismutase (SOD), catalase, the reduced form of glutathione (GSH), glutathione peroxidase, gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 42 publications
1
69
0
1
Order By: Relevance
“…NQO1 also catalyzes the regeneration of oxidized vitamin E, contributing to the maintenance of these important antioxidants (41). It has been demonstrated that NQO1 is strongly induced by SF in different tissues, such as the rat bladder, animal and human mammalian tissues (9,61), and cell lines, such as bronchial epithelial cells, rat aortic smooth muscle cells, and cardiac fibroblasts (48,62,63). To our knowledge, no studies have evaluated whether physical exercise affects NQO1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…NQO1 also catalyzes the regeneration of oxidized vitamin E, contributing to the maintenance of these important antioxidants (41). It has been demonstrated that NQO1 is strongly induced by SF in different tissues, such as the rat bladder, animal and human mammalian tissues (9,61), and cell lines, such as bronchial epithelial cells, rat aortic smooth muscle cells, and cardiac fibroblasts (48,62,63). To our knowledge, no studies have evaluated whether physical exercise affects NQO1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…and those reported by others 3,4) might be due to the cells, but not to the kinds of isothiocyanate compounds used in the experiments. In addition, preferential augmentation of Gclm mRNA expression by 6-MITC was also observed in adherent peritoneal exudate cells.…”
mentioning
confidence: 44%
“…1) Further, sulforaphane augments the expression of an antioxidant gene, gamma-glutamate cysteine ligase [1][2][3] and results in a transient decrease in cellular reduced glutathione levels, followed by increases in its levels. 3,4) 6-(Methylsulfinyl)hexyl isothiocyanate (6-MITC) is found in a Japanese pungent spice, wasabi (Wasabia japonica), 5) and has been found to augment the induction of phase2 enzymes, such as quinone reductase (QR) and glutathione S-transferase (GST), by stimulating expression of their genes. 6,7) Little work, however, has been done on the effects of 6-MITC on cellular glutathione levels.…”
mentioning
confidence: 99%
“…However, growing evidence suggests that protection against ROS accumulation can occur through increased expression of mitochondrial antioxidant enzymes, e.g., SOD2, or proteins responsible for the biosynthesis of glutathione and for the reduction of NADP + . Levels of SOD2 and mitochondrial glutathione peroxidase and reductase and glutathione are elevated by treatment of aortic smooth muscle cells and cardiac myocytes with sulforaphane [103] or dithiolethione, another organosulfur compound [104]. While these effects have not yet been reported for mitochondria present within neurons or the CNS, preliminary results from our lab support this hypothesis and demonstrate that mitochondria from the brains of rats treated with sulforaphane are resistant to t-butyl hydroperoxide-induced opening of the PTP [71].…”
Section: S433mentioning
confidence: 97%